Pengaruh Kenaikan Cukai Hasil Tembakau, Biaya Produksi, Dan Volume Penjualan Terhadap Profitabilitas PT Gudang Garam TBK. (Periode 2020-2024) - Muhammad Abdul Rozak Al Hamam; Mohammad Rizal; Satria Putra Utama (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the impact of increases in tobacco excise taxes, production costs, and sales volume on the profitability of PT Gudang Garam Tbk during the 2020–2024 period. This study employs a quantitative approach using secondary data obtained from the company’s financial statements, analyzed via multiple linear regression using EViews software. The results indicate that, simultaneously, the variables of tobacco excise tax increases, production costs, and sales volume influence profitability. However, individually, these three variables do not significantly affect profitability. The coefficient of determination indicates that the independent variables explain 53.64% of the variation in profitability, while the remaining 46.36% is influenced by other variables outside the research model. These results suggest that the company is able to make adjustments through pricing strategies, cost efficiency, and sales management, thereby minimizing the impact of excise tax increases and production costs on profitability. Keywords: Tobacco Excise Tax, Production Costs, Sales Volume, Profitability